(untitled) (International Journal of Contemporary Security Studies, 2023)
In the Republic of Serbia, the assessment of losses and damages after a natural disaster is based on a document adopted in 1987 during the Socialist Federal Republic of Yugoslavia. Although of exceptional quality in its structure and purpose, the Instruction on a Uniform Methodology for Assessing Damage from Natural Disasters has outlived its time and it is necessary to align the document with today’s needs. The Government of the Republic of Serbia has formed a working group with the task of drafting a unique methodology for assessing damage from natural and other disasters, which is also in line with international standards and practice. In parallel with this activity, engineering associations and groups of experts are working on technical instructions for each of the natural hazards, which will be compatible with the unique methodology to be adopted by the Government of Serbia. The earthquake that hit the Republic of Croatia in 2020 pointed out a number of shortcomings in domestic documents, and then the international methodology "Post Disaster Need Assessment" was used to assess the damage. The paper presents the experiences of a team of experts from Serbia who paid an official visit to the Republic of Croatia after the earthquakes in Petinja and Zagreb and gained significant experience from the field in damage assessment, as well as through cooperation with crisis headquarters formed after the earthquake.